Blockade of programmed cell death protein 1 (PD-1) in Sézary syndrome reduces Th2 phenotype of non-tumoral T lymphocytes but may enhance tumor proliferation. (1st January 2020) - Saulite, Ieva; Ignatova, Desislava; Chang, Yun-Tsan; Fassnacht, Christina; Dimitriou, Florentia; Varypataki, Eleni; Anzengruber, Florian; Nägeli, Mirjam; Cozzio, Antonio; Dummer, Reinhard; Scarisbrick, Julia; Pascolo, Steve; et al.
ABSTRACT: Sézary syndrome (SS) is an aggressive leukemic variant of cutaneous T-cell lymphoma (L-CTCL) that arises from malignant clonally derived skin-homing CD4 + T cells. Based on advancements in our understanding of the mechanisms underlying L-CTCL, boosting the suppressed immune response emerges as a promising strategy in SS management. Immune checkpoint inhibitory molecules have already demonstrated efficacy in a wide spectrum of malignancies. Currently, agents targeting the programmed death-1 (PD-1) axis are under evaluation in L-CTCL. Here we investigated the expression of PD-1 and its ligands, PD-L1 and PD-L2 in blood and skin from patients with L-CTCL. We demonstrate that PD-1 expression is markedly increased on tumor T cells compared to non-tumor CD4 + T cells from SS patients and to CD4 + cells from healthy individuals. In contrast, PD-L1 shows decreased expression on tumor T cells, while PD-L2 expression is low without significant differences between these groups. Functional PD-1 blockade in vitro resulted in reduced Th2 phenotype of non-tumor T lymphocytes, but enhanced the proliferation of tumor T cells from SS patients. Our study sheds some light on the PD-1 axis in both peripheral blood and skin compartments in SS patients, which may be relevant for the treatment of L-CTCL with immune checkpoint inhibitor.